2017
DOI: 10.1149/2.1541714jes
|View full text |Cite
|
Sign up to set email alerts
|

Room Temperature Oxidation of Ti3C2MXene for Supercapacitor Electrodes

Abstract: Two kinds of Ti 3 C 2 /TiO 2 hybrids were synthesized by room temperature oxidation methods, named as Ti 3 C 2 /TiO 2 -nanoparticles and Ti 3 C 2 /TiO 2 -nanowires, respectively. Effects of reaction time and concentration of NaOH solution on the microstructures and electrochemical performances of Ti 3 C 2 /TiO 2 composites were studied in details. When used as electrodes for supercapacitors, both Ti 3 C 2 /TiO 2 -nanoparticles and Ti 3 C 2 /TiO 2 -nanowires exhibit enhanced supercapacitive performances. The el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
104
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(114 citation statements)
references
References 48 publications
7
104
0
3
Order By: Relevance
“…Besides, from the O 1s spectra, the peak of OTi was greatly increased for the TiO 2 /Ti 3 C 2 T x than the Ti 3 C 2 T x . [57] The energy dispersive X-ray (EDX) characterization revealed that the atomic ratio of Ti/O in the TiO 2 /Ti 3 C 2 T x sample was higher than that in Ti 3 C 2 T x , again confirming the generation of the TiO 2 ( Figure S5, Supporting Information). The specific surface areas (SSA) of the Ti 3 C 2 T x and TiO 2 /Ti 3 C 2 T x samples were further characterized through the Brunauer-Emmett-Teller (BET) analysis ( Figure 1H).…”
mentioning
confidence: 83%
“…Besides, from the O 1s spectra, the peak of OTi was greatly increased for the TiO 2 /Ti 3 C 2 T x than the Ti 3 C 2 T x . [57] The energy dispersive X-ray (EDX) characterization revealed that the atomic ratio of Ti/O in the TiO 2 /Ti 3 C 2 T x sample was higher than that in Ti 3 C 2 T x , again confirming the generation of the TiO 2 ( Figure S5, Supporting Information). The specific surface areas (SSA) of the Ti 3 C 2 T x and TiO 2 /Ti 3 C 2 T x samples were further characterized through the Brunauer-Emmett-Teller (BET) analysis ( Figure 1H).…”
mentioning
confidence: 83%
“…The modes for Ti 3 C 2 T x MXene are located at 128, 219, 385, 618 and 711 cm À1 , comparable to previous reports. [55][56][57] The heterogeneity of the surface terminal groups affect the overall spectrum as a result of collaborative vibrations from surface and central Ti atoms, central C atoms, and the terminal groups -O, -OH and -F. The band at 128 cm À1 (E g ) is indicative of -F terminal groups from in-plane vibrations of surface Ti and C atoms. Out-of-plane stretching vibrations of surface Ti and C atoms give rise to the 219 cm À1 band as a result of -OH terminal groups.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the specic surface area of the sample was further characterized by the Brunauer-Emmett-Teller (BET) method and N 2 adsorption/desorption isotherm analyses (Fig. S7 †), showing that as-exfoliated V 4 C 3 T x have a high BET surface area of 156 m 2 g À1 , which can compare with those of other MXenes, such as Ti 3 C 2 T x of 98 m 2 g À1 , 45 Ti 3 C 2 T x of 4.74 m 2 g À1 , 46 Ti 3 C 2 T x /TiO 2 nanowires of 56.45 m 2 g À1 , 46 etc.…”
Section: Fabrication and Characterization Of V 4 C 3 T X Nanosheetsmentioning
confidence: 98%